Mengembangkan Radio Komunitas Pesantren - Anwari, Anwari (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2013)
This article discusses the use of community radio as the base for scientific actualization along with actualization on culture and tradition of Pesantren. The author argues that the existence of Islamic boarding schools or pesantren that have positive traditions and uniqueness is without a doubt offer advantages to the development of the community radio. Different from profit-oriented radio, community radio of Pesantren that that involves community participation should offer broadcasting programs that expose activities and ideas related to Pesantren. Expectedly, through such pro–grams in the community radio, Islamic teaching will be well known, understood, internalized and at the end will be implemented in the daily lifeas a way of life withinsociety.Keywords: community radio, Islamic boarding school, Islamic teachings, tradition———————————————————————-Artikel ini mendiskusikan pemanfaatan radio komunitas sebagai aktualisasi basis keilmuan, budaya dan tradisi pesantren. Penulis berargumen bahwa keberadaan pesantren yang memiliki tradisi positif dan kekhasan, ten–tunya menjadi keunggulan pesantren dalam pengembangan radio komunitas. Berbeda dengan radio yang berorientasi profit, radio komunitas pesantren yang melibatkan partisipasi komunitas harus membuat program-program siaran yang berisikan kegiatan-kegiatan dan gagasan-gagasan pesantren tentang ajaran Islam agar benar-benar diketahui, dipahami, dihayati dan selanjutnya diamalkan sebagai pedoman hidup masyarakat.Kata Kunci: radio komunitas, pesantren, ajaran Islam, tradisi